Plant growth-promoting microorganisms as mitigators of water stress in pastures: a narrative review (Research, Society and Development, 2022)
Water stress is a reality present in pastoral areas throughout Brazil, and more challengingly in semi-arid regions. These climatic conditions test the tolerance to water stress of the forage species used, which despite their rusticity, markedly decrease their performance in low water availability, which limits the expression of all their productive potential. In this sense, it is important to search for sustainable technologies that help a greater resilience of animal production on pasture and that are beneficial to the environment, such as the use of microorganisms that promote plant growth, which can potentially help these species to tolerate the deleterious effects of water stress. Therefore, the objective of this review was to compile information on the use of plant growth-promoting bacteria, arbuscular mycorrhizal fungi and their co-inoculation with water stress mitigating agents in forage plants. In view of data obtained from research platforms, the effects of inoculations with beneficial soil microorganisms on morphophysiological and productive characteristics of forage plants were addressed and how this symbiosis can potentially help plants to tolerate water stress, in addition to describing the specifics of the tripartite relationship between fungi, bacteria and forage plants. With this review, it was found that the use of microbiological inputs as modulators of species tolerance to drought has potential use, requiring a greater volume of studies to consolidate the technique in a way that strengthens it with a sustainable and resilient alternative of livestock to pasture.